The Analysis of Gothic Architecture
1 online resource
Keywords: The essays in this volume reflect on and build on the remarkable legacies of Robert Mark and Andrew Tallon, who pioneered the application of high-technology research methods to the study of Gothic architecture. Combining personal reminiscences and historiographical discussions with meticulous geometrical and structural analyses based on photogrammetric and laser-scanned building surveys, this book offers valuable new perspectives not only on Mark and Tallon themselves, but also on major churches including the abbeys of Saint-Denis and Alcobaça, Santa Maria Novella in Florence, Notre-Dame in Paris, and the cathedrals of Clermont, Reims and Wells. Contributors are: Sheila Bonde, Robert Bork, Lindsay S. Cook, Michael Davis, James Hillson, Kyle Killian, Peter Kurmann, Clark Maines, Ethan Mark, Stephen Murray, Sergio Sanabria, Dany Sandron, Ellen Shortell, Elizabeth B. Smith, Rebecca Smith, Arnaud Timbert, Stefaan Van Liefferinge, and Nancy Wu.